Papers of Percy Deane - Deane, P. E. (1915)
Typescript reports by Percy Deane during World War I, curriculum vitae of Deane, and newspaper obituary of Deane.
Manuscript reference no.: MS 10096.
National Library of Australia Pictures PIC/12324/1-20.
Percival Edgar Deane (1890-1946) was appointed as private secretary to Prime Minister Hughes in 1916. He attended Imperial Conferences in Britain with Hughes in 1918 and 1921 and with Prime Minister Bruce in 1926. He was a member of and secretary to the Australian delegation to the Versailles peace Conference. He was awarded a CMG in 1921 and became secretary to the Prime Minister's Department in that year. From 1929 until 1932 he was secretary of the Department of Home Affairs. From 1932 until 1936 he was a member of the War Pensions Entitlement Board until retiring due to ill health in 1936.
Selected items exhibited in "WW1" National Library of Australia, 26 November 2014 - 31 May 2015
Keywords: Deane, P. E. -- Archives; Australia. -- Army. -- Australian General Hospital, 1st.; Australia. -- Army. -- Australian Imperial Force (1914-1921); Australia. -- Prime Minister's Department -- Officials and Employees. -- Archives; World War, 1914-1918 -- Egypt -- Personal Narratives; World War, 1914-1918 -- Medical care -- Egypt; Australia -- Officials and employees -- Archives; Army officers; Public officers